(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ksharakalpana is one of the unique pharmaceutical preparation forms described in Ayurveda. Kshara is ashes of herbal drugs and is alkaline in nature. A detailed description of Kshara Kalpana preparation methods, types, properties and applications of different Kshara are available in Ayurvedic classics. Kshara is the substance having Ksharana and Kshanan properties. Various plants are mentioned as suitable for the preparation of Kshara viz., Apamarga, Arka (Calotropis gigantea Linn.), Mulaka (Raphanus sativus Linn.), Snuhi (Euphorbia nerifolia Linn.) etc. Among these Apamarga, Arka are the most common drugs used for the preparation of Kshara. In the present study whole plant of Apamarga (Achyranthes aspera Linn.) was used for the preparation of Kshara. Different opinions are there about the amount of water to be used, number of filtrations etc., while preparing the Kshara. Generally Apamarga kshara is prepared by decantation process in a single wash. In order to obtain increased yield and to reduce the loss during straining, in the present study it was prepared by the capillary action and three times washing. This method gave 49% more yield of Apamarga kshara and is far more when compared to traditional methods. Physicochemical evaluation of the prepared Kshara complied with the pharmacoepial standards.